Pengaruh Strategi Pemasaran terhadap Volume Penjualan Produk Usaha Kecil Dan Menengah di Kota Lhokseumawe - SAHARUDDIN SAHARUDDIN (LPPM Universitas Malikussaleh – Indonesia, 2021)
This study aims to determine the effect of Marketing Strategy on Sales Volume of Aluminum Handicraft Products in Banda Sakti District, Lhokseumawe. For the purposes of data analysis, qualitative and quantitative methods were used. The data used is primary data.The results of the study prove that partially, product variables (X1), price (X2), promotion (X3) Distribution (X4) affect the sales volume of Small and Medium Enterprises Products in Lhokseumawe City. Furthermore, the test results simultaneously prove that the F table of 3.00 is much smaller than the calculated F of 11.044. The Correlation Coefficient (R) is 0.790 or 79.0%, this means that Product (X1), Price (X2), Promotion (X3) and Distribution (X4) factors have a strong relationship with the sales volume of aluminum handicraft products (Y). The coefficient of determination (R2) is 0.624 or 62.4%, this means that the sales volume of small and medium business products is influenced by marketing strategies, the remaining 37.6% is influenced by other variables outside of this study, while the Adjusted R Square is 0.324 or 32.4%, this means the Dependent Variable can be explained by the variation of Product (X1), Price (X2), Promotion (X3) Distribution (X4) which are Independent Variables